ANALYSIS OF RICE FARMING INCOME AND FACTORS INFLUENCING IT IN SINGGARAN DISTRICT, PATI, BENGKULU CITY - Anriana, Nina; Yuliarso, M.Zulkarnain; Utama, Satria Putra; Sari, Puspita (Universitas Veteran Bangun Nusantara, 2025)
One of the sub-districts in Bengkulu City which is the largest rice producer with quite extensive agricultural land is Singgaran Pati Sub-district. However, the area of agricultural land in Singgaran Pati Sub-district has decreased every year due to land conversion, which has an impact on decreasing production volume. This study aims to analyze the amount of rice farming income and the factors that influence it in Singaran Pati Sub-district, Bengkulu City. This study uses descriptive and quantitative methods with a multiple linear regression analysis approach. Sampling in this study used the simple random sampling method which was selected randomly so that each population had the same chance of being selected. The results showed that the average income of rice farmers in Singaran Pati Sub-district was IDR 6,833,753 per planting season. From the results of the analysis, age, number of family dependents and land area had a significant influence on farmer income, while the factors of education level and farming experience showed no influence on farmer income. Keywords: Rice Farming, Income, Farming Factors Abstrak Salah satu Kecamatan di Kota Bengkulu yang merupakan penghasil padi terbesar dengan lahan pertanian yang cukup luas merupakan Kecamatan Singgaran Pati. Namun luas lahan pertanian di Kecamatan Singgaran Pati mengalami penurunan setiap tahun akibat alih fungsi lahan, yang bedampak pada menurunnya jumlah produksi. Penelitian ini bertujuan menganalisis besarnya pendapatan usahatani padi serta faktor-faktor yang mempengaruhinya di Kecamatan Singaran Pati, Kota Bengkulu. Penelitian ini menggunakan metode deskriptif dan kuantitatif dengan pendekatan analisis regresi linier berganda. Pengambilan sampel pada penelitian ini menggunakan metode simple random sampling yang dipilih secara acak agar setiap populasi memiliki peluang terpilih yang sama. Hasil penelitian menunjukkan bahwa rata-rata pendapatan petani padi di Kecamatan Singaran Pati sebesar Rp. 6.833,753 per musim tanam. Dari hasil analisis, umur, jumlah tanggungan keluarga dan luas lahan memiliki pengaruh yang signifikan terhadap pendapatan petani, sedangkan faktor tingkat pendidikan dan pengalaman usahatani menunjukkan tidak adanya pengaruh terhadap pendapatan petani. Kata kunci: Usahatani Padi, Pendapatan, Faktor Usahatani